A description of some leases based on the principle of parliamentary tenant-right - McDonnell, James (Statistical and Social Inquiry Society of Ireland, 1879)
Sir George Campbell, in an admirable pamphlet published in June, 1869, points out with great clearness the de facto state of land tenure in Ireland. He shows that although the legal conditions were at that time substantially the same in both England and Ireland they had seldom in practice been fully acted on or recognised by either landlord or tenant in Ireland. He shows how under this strange condition of things [laws made on the principle of contract only and customs prevailing on the principle of status or tenure] there had sprung up tenant-right in the north, and elsewhere somewhat analogous usages, or at least expectations, any interference with which on the part of the landlord was resented by the tenant, and often led to violence. He thus describes the Ulster custom.
Read before the Society, 28 January 1879
Keywords: Land reform; Irish land question; Tenant rights; Ulster Custom; 314.15